Studies on Oligonuclear Palladium Complexes - Huq, Fazlul; Farhad, Mohammad; Abdullah, Ahmed; Beale, Philip; Zhang, Mei (Asian Journal of Chemistry, 2010)
Two polynuclear palladium complexes, (trans-PdCl(NH3)22 μ-trsans-Pd(NH3)2-(H2N(CH2)6NH2)2]Cl4 (MHI) and [trans-PdCl(NH3)2] μ-trans-Pd(NH3)2(H2N(CH2)5NH2)2]Cl4 (MH2) have been prepared and evaluated for their activity against A2780 and A2780cis-R ovary cell lines using MTT (3-(4,5-dimethyl-2thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide) reduction assay. The interaction of the compounds with pBR322 plasmid DNA and salmon sperm DNA has also been studied using gel electrophoresis. Both MHI and MH2 display a lower activity than cisplatin, MHI being marginally more active than MH2. The compounds are believed to bind to DNA forming interstrand bifunctional adducts and at higher concentrations may also form interhelical bifunctional adducts. The lower anticancer activity of the compounds as compared to cisplatin is believed to be due to their higher reactivity. The Pd-Cl bonds are broken much more readily than Pt-Cl bonds so that unlike BBR3464 or cisplatin, MHI and MH2 are aquated more easily. The resulting aquated species are deactivated due to binding with other biomolecules such as glutathione and metallothionein before they have a chance to bind with DNA.